Pengaruh Ekstrak Etanol Daun Sukun (Artocarpus Altilis (Parkinson Ex F.A. Zorn) Fosberg) terhadap Kadar LDL (Low Density Lipoprotein) pada Mencit Putih Jantan Hiperkolesterol - Helmi Arifin; Zet Rizal; Meri Susilawati (Jurnal Farmasi Higea, 2015)
The research has been about effect of ethanol extract of breadfruit leaves (Artocarpus altillis (Parkinson ex F.A. Zorn) Forsberg) to cholesterol levels in white male mice. Mice used 45 individuals were divided into 5 groups of animal that group I as a negative control group was given only the standard diet food. Group II is the positive control induced hight-fat foods and suspension PTU. Group III, IV and V are given foods containing high fat and suspension PTU with extract variations along with dose of 100, 300, and 900 mg/kg body weight once a day for 7,14 and 21. Then LDL levels measured on day 7, 14, and 21. The results of resarch showed that there are variations influence the dose and duration of administration of the decreased levels of blood LDL white male mice. The highest levels decrease at a dose of 900 mg/kg for 21 day.